Food Sanitation Hygiene Education in Increasing Knowledge and Behavior of Food Handlers at Alhikmah Catering Surakarta - Marfuah, Dewi; Wardana, Agung Setya; Naresti, Faiza (Prosiding University Research Colloquium, 2023)
Hygiene behavior of food handlers is inseparable from attitudes and knowledge regarding food hygiene and sanitation. Knowledge, attitude and personal hygiene of food handlers is very important in food handling so that the food produced is protected from contamination. The purpose of this study was to determine the effect of food sanitation hygiene education on knowledge and hygiene behavior of food handlers at Alhikmah Surakarta Catering. Research method: This type of research is quasi-experimental using a one group pretest posttest design. The sample in this study were food handlers at Alhikmah Surakarta Catering in October 2022. Sampling was carried out by purposive sampling with inclusion criteria, namely food handlers who can read and are willing to be samples, so that the sample in this study was 18 people. Food sanitation hygiene education is carried out every 2 weeks for 3 weeks using leftleat media. Test analysis of differences in knowledge of food handlers before and after food using the Wilcoxon test and test analysis of differences in behavior of food handlers before and after food using the Wilcoxon test. The results of the study showed that the difference in the knowledge of food handlers before and after food sanitation hygiene education obtained a P value = 0.046 and the difference in the behavior of food handlers before and after food sanitation hygiene education obtained a P value = 0.000. Conclusion: There is an increase in the knowledge and behavior of food handlers after being given food sanitation hygiene education at Alhikmah Surakarta Catering.